The Influence of Taxpayer Awareness and Taxation Socialization on Motor Vehicle Taxpayer Compliance in the City of Probolinggo - Soetomo, Fernando Yorhans; Aisyaturrahmi (Universitas Nahdlatul Ulama Surabaya, 2024)
The aim of this research is to see the level of motor vehicle tax compliance in Probolinggo City. A good level of compliance can be achieved if taxpayers are aware of their tax obligations and the government carries out outreach to provide the latest information regarding taxation. This type of research is research using quantitative methods by distributing questionnaires. The population in this study were taxpayers registered with UPT SAMSAT Probolinggo City and the sample used in this study was 400 respondents. The results of this research indicate that taxpayers in Probolinggo City are aware of their tax responsibilities and want more comprehensive socialization so that it can influence taxpayers to better comply with applicable tax regulations.